Politics Design: A Solution-Oriented Approach to Political Science - Sobari, Wawan (UIN Sunan Gunung Djati, 2025)
Post-behavioralist critiques are a crucial foundation for changes in previous apolitical political research. Politics should be an academic instrument and a response to humanity’s challenges. Political design seeks to criticize the dominance of the logic of study that prioritizes analytical and objective methods. This study proposes political design as an alternative approach to Political Science, prioritizing creative and design thinking in addressing public problems. This paper identifies the shortcomings of conventional critical thinking approaches and introduces political design as a practical, solution-oriented method through a literature review method, specifically an integrative review. Politics has been redefined as an instrument for power solutions. This study highlights five core principles: promoting solutions for public problems, moving beyond theoretical frameworks to operational implementation, fostering innovation over ordinary resolutions, managing the interests of designers to protect public values, and grounding practice in the awareness of inherent power imbalances. The results present a synthesis of interdisciplinary literature that informs this new approach, while the conclusion discusses its potential contributions to Political Science.